Detailed functional and structural phenotype of Bietti crystalline dystrophy associated with mutations in CYP4V2 complicated by choroidal neovascularization. (1st October 2016) - Fuerst, Nicole M.; Serrano, Leona; Han, Grace; Morgan, Jessica I. W.; Maguire, Albert M.; Leroy, Bart P.; Kim, Benjamin J.; Aleman, Tomas S.
ABSTRACT: Purpose : To describe in detail the phenotype of a patient with Bietti crystalline dystrophy (BCD) complicated by choroidal neovascularization (CNV) and the response to intravitreal Bevacizumab (Avastin ® ; Genentech/Roche). Methods : A 34-year-old woman with BCD and mutations in CYP4V2 (c.802-8_806del13/p.H331P:c992A>C) underwent a complete ophthalmic examination, full-field flash electroretinography (ERG), kinetic and two-color dark-adapted perimetry, and dark-adaptometry. Imaging was performed with spectral domain optical coherence tomography (SD-OCT), near infrared (NIR) and short wavelength (SW) fundus autofluorescence (FAF), and fluorescein angiography (FA). Results : Best-corrected visual acuity (BCVA) was 20/20 and 20/60 for the right and left eye, respectively. There were corneal paralimbal crystal-like deposits. Kinetic fields were normal in the peripheral extent. Retinal crystals were most obvious on NIR-reflectance and corresponded with hyperreflectivities within the RPE on SD-OCT. There was parafoveal/perifoveal hypofluorescence on SW-FAF and NIR-FAF. Rod > cone sensitivity loss surrounded fixation and extended to 10° of eccentricity corresponding to regions of photoreceptor outer segment-retinal pigmented epithelium (RPE) interdigitation abnormalities. The outer nuclear layer was normal in thickness. Recovery of sensitivity following a 76% rhodopsin bleach was normal. ERGs were normal. A subretinal hemorrhage in the left eye co-localized with elevation of the RPE on SD-OCT and leakage on FA, suggestive of CNV. Three monthly intravitreal injections of Bevacizumab led to restoration of BCVA to baseline (20/25). Conclusion : crystals in BCD were predominantly located within the RPE. Photoreceptor outer segment and apical RPE abnormalities underlie the relatively extensive retinal dysfunction observed in relatively early-stage BCD. Intravitreal Bevacizumab was effective in treating CNV in this setting.